AB051. SOH26AB_0087. Management of anastomotic biliary strictures post orthotopic liver transplantation: a 4-year review - Start, Alex; Hegarty, Cormac; Ahmad, Afaf; Mulcahy, Hugh; Donnellan, Fergal; Hamid, Mohamed; Hoti, Emir; Dillon, Audrey (Mesentery and Peritoneum, 2026)
Anastomotic biliary strictures are a common complication of orthotopic liver transplantation (OLT), resulting in significant morbidity and mortality. Current management strategies suggest endoscopic retrograde cholangiopancreatography (ERCP) as first line, followed by drain insertion, and surgical reconstruction, hepaticojejunostomy (hep-jej). The aim of this study is to evaluate the management approaches to post-OLT anastomotic strictures in Ireland’s National Liver Unit (January 2019–October 2023).